A system for three-dimensional dosimetric verification of treatment plans in intensity-modulated radiotherapy with heavy ions - Karger, Christian; Jäkel, Oliver; Hartmann, Günther H.; Heeg, Peter (Medical physics, 1999)
The introduction of dynamic intensity modulation into radiotherapy using conventional photon beams or scanning particle beams requires additional and efficient methods of dose verification. Dose measurements in dynamically generated dose distributions with a single ionization chamber require a complete application of the treatment field for each single measurement. Therefore measurements are performed by simultaneous use of multiple ionization chambers. The measurement is performed by a computer controlled system and is comprised of the following steps: (a) automated positioning of the ionization chambers, (b) measurement at these points, (c) a comparison with the calculated dose from the treatment planning system, and (d) documentation of the measurement. The ionization chambers are read out by a multichannel electrometer and are densely packed into a mounting of polymethylmetacrylate, which is attached to the arm of a three-dimensional motor- driven water phantom. The measured and planned dose values are displayed numerically as well as graphically. The mean deviation between measured and planned doses as well as their standard deviation are calculated and displayed. Through printouts complete documentation of the measurement is obtained and a quick decision can be made whether the dose distribution is acceptable for the patient. The system is now routinely used for dose verification at the heavy ion therapy project at the Gesellschaft für Schwerionenforschung in Darmstadt. Up to now 242 measurements have been performed for heavy ion treatment of 30 patients. The system allows efficient verification and documentation of carbon ion fields and is in principle also applicable to intensity-modulated photon beams.